STRENGTHENING ATMOSPHERIC EMISSIONS IN THE COLISION OF COMET SHOEMAKER-LEVY 9WITH THE PLANET JUPITER: STRENGTHENING ATMOSPHERIC EMISSIONS IN THE COLISION OF COMET SHOEMAKER-LEVY 9WITH THE PLANET JUPITER - Adeishvili, Teimuraz; Aleksandrov, Alksandar; Okrochelidze, Nino; Khvedelidze, Leonardo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The phenomena of incrsing intensity of atomic oxygen lines λ=5577Å and λ=6300Å  during collition of Shumakher-Leve 9 comet with the Jupiter are considered. The corresponding physical mechanisms of generation of those glow are presented.